Analysis the prognostic values of solute carrier (SLC) family 39 genes in gastric cancer - Ding, Bisha (Am J Transl Res, 2019)
Background: Gastric cancer (GC) is one of the most common diagnosed cancer with poor prognosis. Solute carrier (SLC) family 39 genes encode membrane transport proteins, which control the influx of zinc and may play important roles in human disease including cancer. However, the prognostic value of individual SLC family 39 gene in gastric cancer patients remain unclear. Methods: Genetic alteration frequency and mRNA expression level of SLC family 39 genes in GC were first assessed by using many online databases including cBioportal for Cancer Genomics, Oncomine, UCSC Xena browser and Ualcan database. The prognostic value of individual SLC family 39 gene in GC patients were further investigated via Kaplan-Meier plotter. Results: The analytic results of genetic alteration frequency showed that mRNA deregulation was one of the most important single factors for alteration in different kinds of gastric cancer. Compared with normal gastric tissues, 14 SLC family 39 genes were all significantly upregulated in GC tissue in Ualcan database, and SLC39A4, SLC39A5, SLC39A6, SLC39A10 mRNA expression were also higher in Oncomine database. The survival analysis indicated that most members of SLC family 39 genes were closely related with prognosis of GC patients, SLC39A7, SLC39A11, SLC39A14 were significantly associated with favorable overall survival (OS), the rest of SLC family 39 genes were importantly correlated with unfavorable OS except SLC39A10. Conclusion: Our analysis identified that 14 SLC family 39 genes are potential prognostic biomarkers of GC patients, and may offer effective and new strategies for GC therapy.